2018
DOI: 10.7554/elife.36491
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the in vitro developmental program of Hammondia hammondi reveals a link between stress sensitivity and life cycle flexibility in Toxoplasma gondii

Abstract: Most eukaryotic parasites are obligately heteroxenous, requiring sequential infection of different host species in order to survive. Toxoplasma gondii is a rare exception to this rule, having a uniquely facultative heteroxenous life cycle. To understand the origins of this phenomenon, we compared development and stress responses in T. gondii to those of its its obligately heteroxenous relative, Hammondia hammondi and have identified multiple H. hammondi growth states that are distinct from those in T. gondii. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(72 citation statements)
references
References 59 publications
(116 reference statements)
0
72
0
Order By: Relevance
“…H. hammondi was first discovered in the feces of a cat in Iowa, USA in 1975 [19], and while morphologically indistinguishable from T. gondii, H. hammondi has a comparatively restricted natural intermediate host range (being incapable of infecting birds) [20,21]. Prior work shows that H. hammondi shares >95% of its~8000 genes in near perfect synteny with T. gondii and expresses functional orthologs of key T. gondii effectors such as ROP18 and ROP5 [22,23]. This is important from an epidemiological and evolutionary perspective, as H. hammondi is not known to cause clinical disease in any naturally infected intermediate (human and other animals) or definitive host [20].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…H. hammondi was first discovered in the feces of a cat in Iowa, USA in 1975 [19], and while morphologically indistinguishable from T. gondii, H. hammondi has a comparatively restricted natural intermediate host range (being incapable of infecting birds) [20,21]. Prior work shows that H. hammondi shares >95% of its~8000 genes in near perfect synteny with T. gondii and expresses functional orthologs of key T. gondii effectors such as ROP18 and ROP5 [22,23]. This is important from an epidemiological and evolutionary perspective, as H. hammondi is not known to cause clinical disease in any naturally infected intermediate (human and other animals) or definitive host [20].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…This is important from an epidemiological and evolutionary perspective, as H. hammondi is not known to cause clinical disease in any naturally infected intermediate (human and other animals) or definitive host [20]. In addition, in tissue culture H. hammondi replicates for a short period of time and then enters into a unique terminally differentiated bradyzoite state that is a) unable to be subcultured in vitro, b) incapable of infecting an intermediate mouse host and c) only capable of infecting a feline host [20,23]. Paradoxically, despite this natural bradyzoite developmental program and expression of canonical bradyzoite genes during tachyzoite-like replication [23,24], H. hammondi cannot be induced to form bradyzoites using stresses like high pH medium that robustly induce cyst formation in T. gondii [23].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore these data, we compared the cluster of T. gondii genes with higher abundance in type II TINs versus type III TINs transcriptomes with published transcript abundance from a different type III strain (VEG) after bradyzoite conversion via high pH ( Fig. 5C; data taken from Sokol et al 52 ). In this comparison, we found that many of the genes in the higherin-type II TINs cluster were also induced in VEG bradyzoites compared to tachyzoites.…”
Section: Parasite Transcripts Are Primarily Found In Tins Transcriptomementioning
confidence: 99%
“…In this comparison, we found that many of the genes in the higherin-type II TINs cluster were also induced in VEG bradyzoites compared to tachyzoites. When we performed Gene Set Enrichment Analysis (GSEA) 53 using the previously published data 52 to create "bradyzoite" and "tachyzoite" gene sets, we found significant enrichment of the bradyzoite gene set in type II TINs transcriptome and the tachyzoite gene set in type III TINs transcriptome ( Fig. S3B).…”
Section: Parasite Transcripts Are Primarily Found In Tins Transcriptomementioning
confidence: 99%